2017
DOI: 10.1007/s11249-017-0858-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temperature and Frequency on Fretting Wear of a Like-on-Like Stainless Steel Contact

Abstract: The influences of environmental temperature and fretting frequency on the mechanisms and rates of wear in a like-on-like 304 stainless steel contact were examined and mainly attributed to changes in the mechanical response of the bulk material and to changes in the behaviour of the oxide debris formed in the fretting process. At low temperatures, wear proceeds by continual oxide formation and egress from the contact, whilst at high temperatures, the rate of wear is much reduced, associated with the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Previous work [28,30] has suggested that the frequency of fretting primarily affects the wear processes in two main ways. Firstly, changes in frequency influence the rate of power dissipation in the contact, thereby influencing temperature; the temperature of the contact itself affects (i) the tendency for the debris to be retained in the contact and form a coherent bed; (ii) the mechanical properties of the substrate material; (iii) the rate at which oxide forms from the metallic surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work [28,30] has suggested that the frequency of fretting primarily affects the wear processes in two main ways. Firstly, changes in frequency influence the rate of power dissipation in the contact, thereby influencing temperature; the temperature of the contact itself affects (i) the tendency for the debris to be retained in the contact and form a coherent bed; (ii) the mechanical properties of the substrate material; (iii) the rate at which oxide forms from the metallic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also observed for the same material the temperature at which such a protective debris layer formed to be dependent on frequency, attributing this effect to the competing effects of rate of oxidation, inter-pass time between fretting strokes and the influence of temperature on agglomeration of oxide debris. In the latter work the rate of surface damage in fretting was linked to plastic deformation of the bulk material (affected by changes in mechanical properties), and the balance of abrasive and protective roles of wear debris, in turn affected by the balance of oxide formation and agglomeration as influenced by temperature and fretting frequency [30].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to buildup of thicker oxide layer on the surface and consequently a larger quantity of easily ejected oxide debris. According to Jin et al (2017) [29], an increase in the fretting frequency results in a reduction in the inter-pass time which is the time between asperity interactions for a given asperity. This in turn lessens the oxide formation per cycle which hence reduces abrasion and may also inhibit the formation of the debris bed at the same time.…”
Section: Frequencymentioning
confidence: 99%
“…A recent research on the high strength alloy steel S132 reported that the transition temperature, under which range the wear coefficient and CoF decrease significantly with increasing the temperature, related to the displacement amplitude [Hayes and Shipway (2017)]. Based on the study of 304 stainless steel on fretting wear, the fretting frequency affects the transition temperature [Jin, Shipway and Sun (2017)]. Besides steel, the loading conditions (displacement amplitude, temperature, the effect of the normal load, the frequency and the contact size) were also studied on Ti-6Al-4V contact [van Peteghem, Fouvry and Petit (2011); Fouvry, Arnaud, Mignot et al (2017)].…”
Section: Experimental Study Of Fretting Wear 21 Wear Mechanismmentioning
confidence: 99%
“…This contact solver based on conjugate gradient method and optimized fast Fourier transfer techniques reduce computation time. Kasarekar et al [Kasarekar, Bolander, Sadeghi et al (2007)] proposed a numerical method for simulating fretting wear with rough surfaces. Results from sinusoidal rough and random rough surfaces indicate roughness plays a significant role in wear process.…”
Section: Other Numerical Models For Fretting Wearmentioning
confidence: 99%